Product service system innovation in the smart city. (February 2018) - Cook, Matthew
Product service systems (PSS) may usefully form part of the mix of innovations necessary to move society towards more sustainable futures. However, despite such potential, PSS implementation is highly uneven and limited. Drawing on an alternate sociotechnical perspective of innovation, this article provides fresh insights on, among other things, the role of context in PSS innovation, to address this issue. Case study research is presented focusing on a use-orientated PSS in an urban environment: the Copenhagen city bike scheme. The article shows that PSS innovation is a situated complex process, shaped by actors and knowledge from other locales. It argues that further research is needed to investigate how actors' interests shape PSS innovation. It recommends that institutional spaces should be provided in governance landscapes associated with urban environments to enable legitimate PSS concepts to co-evolve in light of locally articulated sustainability principles and priorities.